Perbandingan Kekuatan Kolom Berdasarkan SNI 2847:2013 dan SNI 2847:2019 - Ahmad Hernadi; Rini Sahara; Septa Utami Dewi (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2021)
Today, Practitioners of Civil Engineering in Indonesia are still using SNI 2847:2013 as code for reinforcement concrete design. As we know that SNI 2847:2019 been published, but practitioners still not yet use it.The point of design and evaluation in SNI 2847 code is reduction factor (ɸ) that could influence strength design of structure base on it behaviour. Load in Column is not just axial load, but flexural and combine of axial and flexural. This behavior makes the column has variate reduction factor and it can shown by interaction diagram. This research is compare between SNI 2847:2013 and SNI 2847:2019 for column with section 400x500, fc’ 20 MPa and reinforcement ratio 1%. Result of this research is compare between SNI 2847:2013 and SNI 2847:2019 for column with variation fy is not too significant. So when the column of SNI 2847:2013 inspected or evaluated by SNI 2847:2019 is not distinction.